Bioequivalence of losartan/amlodipine fixed dose combination tablets (losanet AM) compared with concomitant administration of Single components of losartan and amlodipine tablets in healthy human volunteers - Bustami, Rana (2015)
A fixed dose combination of losartan, an angiotensin receptor blocker and amlodipine, a calcium channel blocker, can potentially provide complementary mechanism of action to improve blood pressure control and clinical outcomes. The current study was conducted to compare the pharmacokinetics of a new combination product of losartan potassium and amlodipine besylate with separate co-administration of losartan potassium and amlodipine besylate tablets in 40 healthy human volunteers after a single oral dose in a randomized three-period crossover study. The study protocol was prepared in accordance to the requirements set in the EMA guidance for conducting bioequivalence studies. Reference (Cozaar 100 mg, Merck Sharp & Dohme Ltd, UK and Norvasc 10 mg, Pfizer, Canada) and test (Losanet AM, Pharmaline, Lebanon) drugs were administered to fasted volunteers and blood samples were collected up to 168 hours and assayed for losartan, carboxylic acid losartan metabolite and amlodipine using a validated LC-MS/MS method. The pharmacokinetic parameters AUC0-t, AUC0- ∞,Cmax, Tmax, T1/2, MRTinf, residual area (%) and elimination rate constant were determined from plasma concentration-time profile by non-compartmental analysis method using WinNonlin V5.3. The analysis of variance did not show any significant difference between the two formulations and 90% confidence intervals fell within the acceptable range for bioequivalence (80-125%). The resulting data demonstrated that when administered as fixed dose combination or individual tablets, the pharmacokinetics of losartan and amlodipine were bioequivalent and were well-tolerated.